1989
DOI: 10.1148/radiology.173.3.2682771
|View full text |Cite
|
Sign up to set email alerts
|

Portal blood flow: measurement with MR imaging.

Abstract: Portal blood flow was measured by means of direct bolus imaging (DBI), a method of measuring flow velocity with magnetic resonance imaging. DBI allows immediate visualization of fluid movement, thereby enabling calculation of a flow velocity from fluid displacement. In a study of 14 healthy male volunteers, portal blood flow was measured with electrocardiographic gating during the 18 seconds subjects could suspend respiration. These measurements showed a close correlation (r = .968) with those obtained by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…[4][5][6][7][8][9] In healthy subjects, Burkart et al 7 and Lycklama à Nijeholt et al 8 measured mean blood flow in the main portal vein and found a rate of 1.2 l/min under basal fasting conditions during normal respiration. In our previous 9 and present studies, mean blood flow in the main portal vein under fasting conditions in the healthy controls during normal during normal respiration was 1.3 l/ min, showing good agreement for results in healthy subjects.…”
Section: Portal Blood Flow In Healthy Controls and Cirrhotics And Efmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9] In healthy subjects, Burkart et al 7 and Lycklama à Nijeholt et al 8 measured mean blood flow in the main portal vein and found a rate of 1.2 l/min under basal fasting conditions during normal respiration. In our previous 9 and present studies, mean blood flow in the main portal vein under fasting conditions in the healthy controls during normal during normal respiration was 1.3 l/ min, showing good agreement for results in healthy subjects.…”
Section: Portal Blood Flow In Healthy Controls and Cirrhotics And Efmentioning
confidence: 99%
“…More recent studies have demonstrated that a cine phase-contrast magnetic resonance (MR) velocity mapping method can noninvasively measure quantitative blood flow in the portal venous system throughout the cardiac cycle during normal respiration. [4][5][6][7][8][9] In this study, we investigated changes in flow velocity and flow volume in the main portal vein under basal fasting conditions while subjects were breath-holding after maximal inspiration or expiration, and compared this with portal blood flow during normal respiration. Blood flow measurements using MR imaging were made in healthy controls and portal hypertensive cirrhotics and the results were compared.…”
Section: Introductionmentioning
confidence: 99%
“…A number of sophisticated modeling approaches employing multiple tracers have been developed for estimating the appearance of an oral glucose load (15,16) but, to date, have not been used in studies of portal glucose sensing in humans. Further confounding estimates of portal glucose concentration is the wide range of values reported for human portal blood flow, (10 -18 ml ⅐ kg Ϫ1 ⅐ min Ϫ1 [17]), which may increase substantially in response to oral glucose ingestion.…”
mentioning
confidence: 99%
“…Magnetic resonance (MR) imaging, by means of time‐of‐flight or phase contrast angiography, can document the size and direction of the flow in a vessel, in a similar way to Doppler ultrasound examination. 52 This is an easy method for the detection of spontaneous portosystemic collaterals. Quantification can be obtained by Cine‐Phase Contrast flow measurements.…”
Section: Introductionmentioning
confidence: 99%